2013
DOI: 10.1007/s00216-012-6652-9
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro metabolism of a novel β2-adrenoceptor agonist, trantinterol: metabolites isolation and identification by LC-MS/MS and NMR

Abstract: Trantinterol is a novel β(2)-adrenoceptor agonist used for the treatment of asthma. The aim of this study is to identify the metabolites of trantinterol using liquid chromatography tandem mass spectrometry (LC-MS/MS), to isolate the main metabolites, and confirm their structures by nuclear magnetic resonance (NMR). Urine, feces, bile, and blood samples of rats were obtained and analyzed. Reference standards of six metabolites were achieved with the combination of chemical synthesis, microbial transformation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Trantinterol-COOH was extracted from acidified samples and then trantinterol, N-OH-trantinterol and tert-OH-trantinterol was extracted from alkalized samples. Our group once used SPE to extract trantinterol and its metabolites from rat urine [2] and it is well known that SPE offers clean extracts, which is of great benefit to the expensive UPLC column. Therefore, SPE was considered.…”
Section: Methods Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Trantinterol-COOH was extracted from acidified samples and then trantinterol, N-OH-trantinterol and tert-OH-trantinterol was extracted from alkalized samples. Our group once used SPE to extract trantinterol and its metabolites from rat urine [2] and it is well known that SPE offers clean extracts, which is of great benefit to the expensive UPLC column. Therefore, SPE was considered.…”
Section: Methods Developmentmentioning
confidence: 99%
“…It has exhibited both a potent trachea relaxing activity and high ␤ 2 selectivity with low cardiac side effect [1]. The arylhydroxylamine trantinterol (N-OH-trantinterol), the tert-butyl hydroxylated trantinterol (tert-OH-trantinterol) and the 1-carbonyl trantinterol (trantinterol-COOH) are the major metabolites of trantinterol in vivo [2].…”
Section: Introductionmentioning
confidence: 99%
“…1b) with concentrations higher than all the other metabolites and trantinterol itself. Therefore, SPFF COOH is the major metabolite after oral administration of trantinterol [3,4]. To further characterize the pharmacokinetic and pharmacodynamic profiles of trantinterol, the quantification method with selectivity and sensitivity for determination of trantinterol and its major circulating metabolite in plasma is indispensable in order to evaluate the efficacy and safety of these compounds after administration of trantinterol to rat.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical trials have revealed that trantinterol is a potent and highly selective β 2 -adrenoceptor agonist with long duration of action and low cardiac side effects 7,8 . The metabolic pathways and pharmacokinetics of trantinterol have recently been reported 9,10 . An in vitro study showed that trantinterol did not produce clinically significant cytochrome P450 inhibition or induction 11 , but its interaction with P-gp has not been characterized.…”
Section: Introductionmentioning
confidence: 99%